Hubungan Modal Psikologis dengan Kinerja Perawat Pelaksana - Fransiska, Rosa Berlina; Nasution, Siti Zahara; Ashar, Taufik (Journal of Telenursing (JOTING), 2024)
This research aimed to analyze the psychological relationship with the performance of executive nurses at the Prof. Mental Hospital. Dr. Muhammad Ildrem Medan in 2023. Quantitative type of research with a cross-sectional design. The population in this study were all executive nurses who worked in the mental inpatient ward at the Prof. Mental Hospital. Dr. Muhammad Ildrem Medan as many as 90 people. The sampling technique used simple random sampling so that 48 people were obtained. Data collection techniques used the Psychological Capital Questionnaire (PCQ) questionnaire with 24 items to measure psychological capital and the nurse performance questionnaire with 25 items. The data that has been obtained will be analyzed univariate and bivariate using the pearson correlation test. The research results showed that the significance value of the psychological capital variable and the performance variable of the implementing nurse was 0.000 (p<0.05). In conclusion, there is a significant positive relationship between psychological capital and the performance of implementing nurses at the Prof. Mental Hospital. Dr. Muhammad Ildrem Medan, where the more positive psychological capital one has, the higher the performance of implementing nurses. Keywords: Executive Nurse, Performance, Psychological.